2016
DOI: 10.3339/jkspn.2016.20.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems and Daytime Sleepiness in Children with Nocturnal Enuresis

Abstract: Nocturnal enuresis (NE) is one of the most common problems in childhood. NE has a multifactorial etiology and is influenced by sleep and arousal mechanisms. The aim of the present study was to prospectively evaluate sleep problems and patterns in children with NE compared with normal healthy controls. Methods: Twenty-eight children with NE and 16 healthy controls were included in the study. To evaluate sleep habits and disturbances, parents and children filled out a questionnaire that included items about slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…40 However, according to Gu et al, there was no significant difference in sleep architecture between children with nocturnal enuresis and healthy controls. 41 In our study, REM sleep percentage was low in children with nocturnal enuresis compared with controls. This polysomnographic finding may be explained by the first-night effect.…”
Section: Polysomnographic Findings In Nocturnal Enuresismentioning
confidence: 39%
“…40 However, according to Gu et al, there was no significant difference in sleep architecture between children with nocturnal enuresis and healthy controls. 41 In our study, REM sleep percentage was low in children with nocturnal enuresis compared with controls. This polysomnographic finding may be explained by the first-night effect.…”
Section: Polysomnographic Findings In Nocturnal Enuresismentioning
confidence: 39%
“…Some studies have demonstrated that children who suffered from enuresis have disrupted sleep with several intermittent arousals that result in fragmentation of sleep and poor quality of sleep [20]. Some previous studies have shown an association between sleep disturbance and NE [21], which confirmed with Nevéus' report stating that the sleep problem is closely related to the pathophysiology of nocturnal enuresis [22]. Children suffered from NE may have a high threshold of cortical arousability, so they will not wake up when the bladder reaches its maximum capacity.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, children who have enuresis are more likely to have periodic limb movements and OSA. As the etiology of NE is unclear and complicated, it makes the treatment lengthy and frequently accompanied by relapses [ 7 ]. NE may occur in children with obstructive SDB due to the decrease in the arousal response [ 8 ].…”
Section: Introductionmentioning
confidence: 99%